Progress of the Plan - A Short Survey of the Working of the Five Year Plan from April 1951 to September 1953 - Planning Commission (Planning Commission, 1951)
The objectives of the Five Year Plan have been set out in detail in the Report. Briefly, these objectives aim at initiating a process of development which will raise living standards and open out to the people new opportunities for a richer and more varied life. This implies: - (i) the provision of increased employment and production by the most efficient utilization of the resources of the country, and (ii) the achievement of the largest measure of social justice possible.
Government of India Planning Commission